PERFIL BIOQUÍMICO SANGUÍNEO HEPÁTICO Y RENAL EN EL SAJINO (Tayassu tajacu) CRIADO EN CAUTIVERIO EN LA AMAZONÍA PERUANA - Schettini Z., Luigi (2005)
The objective of this study was to establish reference serum values for bilirrubin (total and direct), alanine amino transferase (ALT), aspartate amino transferase (AST), alkaline phosphatase, cholesterol, total protein, albumin, urea, and creatinine in healthy collared peccary (Tayassu tajacu) kept under captivity in the Amazonian jungle of Peru (Loreto, Iquitos). A total of 28 adult animals (14 males and 14 females) were used. Blood samples (7 ml) were collected from the safen vein. Serum values were: Total bilirrubin: 0.7 ± 0.2 mg/dl; direct bilirrubin: 0.2 ± 0.1 mg/dl; ALT: 26.5 ± 9.1 UI/l; AST: 15.9 ± 8.4 UI/l; alkaline phosphatase: 27.5 ± 15.5 UI/l; cholesterol: 94.4 ± 20.2 mg/dl; total protein: 8.5 ± 1.1 g/dl; albumin: 4.4 ± 0.5 g/dl; urea: 58.1 ± 11.1 mg/dl; and creatinine: 2.2 ± 0.5 mg/dl. It was concluded that serum values were similar to other results reported in the literature and without statistical differences due to sex.